Weight gain as a risk factor for progressive neurochemical abnormalities in first episode mania patients: a longitudinal magnetic resonance spectroscopy study. Issue 16 (12th December 2022) - Bond, David J.; Silveira, Leonardo E.; Torres, Ivan J.; Lam, Raymond W.; Yatham, Lakshmi N.
Abstract: Background: We previously reported that bipolar disorder (BD) patients with clinically significant weight gain (CSWG; ⩾7% of baseline weight) in the 12 months after their first manic episode experienced greater limbic brain volume loss than patients without CSWG. It is unknown whether CSWG is also a risk factor for progressive neurochemical abnormalities. Methods: We investigated whether 12-month CSWG predicted greater 12-month decreases in hippocampal N -acetylaspartate (NAA) and greater increases in glutamate + glutamine (Glx) following a first manic episode. In BD patients ( n = 58) and healthy comparator subjects (HS; n = 34), we measured baseline and 12-month hippocampal NAA and Glx using bilateral 3-Tesla single-voxel proton magnetic resonance spectroscopy. We used general linear models for repeated measures to investigate whether CSWG predicted neurochemical changes. Results: Thirty-three percent of patients and 18% of HS experienced CSWG. After correcting for multiple comparisons, CSWG in patients predicted a greater decrease in left hippocampal NAA (effect size = −0.52, p = 0.005). CSWG also predicted a greater decrease in left hippocampal NAA in HS with a similar effect size (−0.53). A model including patients and HS found an effect of CSWG on Δleft NAA ( p = 0.007), but no diagnosis effect and no diagnosis × CSWG interaction, confirming that CSWG had similar effects in patients and HS. Conclusion: CSWG is a risk factor for decreasing hippocampal NAA in BD patients and HS. These results suggest that the well-known finding of reduced NAA in BD may result from higher body mass index in patients rather than BD diagnosis.